Consumer preferences for evaluative front-of-package nutrition labels: evidence from a choice experiment in China - Yang, Minda; Min, Shi; Nguyen, Trung Thanh (Frontiers in Nutrition, 2025)
This study examines consumer preferences, behaviors, and willingness to pay (WTP) for evaluative front-of-package (FOP) nutrition labels in China, with a particular focus on the role of information provision in influencing consumer behavior. A choice experiment was conducted involving ham sausages with different evaluative nutrition labels, including the Health Star Rating and Nutrition Score System, among 998 participants from five representative cities in China. The choice experiment also incorporates an information intervention to assess its impact on consumers’ choice. A random parameter logit model was employed to estimate consumers preferences and WTP for the different evaluative FOP labels. The results show that consumers exhibit a higher preference for ham sausages with evaluative FOP nutrition labels compared to those without any labels. The Nutrition Score System emerges as the most preferred labeling format. Furthermore, under information intervention, consumers exhibit the highest WTP for evaluative FOP labels, with 2.47 yuan for the Health Star Rating (124% premium) and 2.77 yuan for the Nutrition Score System (138% premium). These findings suggest a substantial demand among Chinese consumers for evaluative FOP nutrition labels and underscore the importance of providing related information to enhance consumer acceptance and promote healthier food-choice behavior.